Innovations, prices, and employment: A theoretical model and an empirical application for West-German manufacturing firms - Wernerr Smolny (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1996)
In this paper, a theoretical model of the impact of product and process innovations on output, capacity utilization, employment, and prices is developed. The model is estimated with micro-data for West German manufacturing firms from the ifo firm panel. The empirical results reveal that innovative firms exhibit a higher utilization and more output and employment growth than noninnovative firms. Innovations also change the market structure. The frequency of price and output changes is lower and the frequency of employment changes is higher in sectors with a large share of product innovators, and vice versa in sectors with a large share of process innovators.
Keywords: C33; D21; O31; 330; Innovations; price setting; market structure